Repetitive transcranial magnetic stimulation for post-stroke depression: An overview of systematic reviews - Gao, Wanning; Xue, Fuyu; Yu, Bin; Yu, Shuo; Zhang, Weimin; Huang, Haipeng (Frontiers in Neurology, 2023)
Objective There is conflicting published research about the clinical effectiveness of repetitive transcranial magnetic stimulation (rTMS) for the treatment of post-stroke depression (PSD). In order to provide trustworthy information for upcoming therapeutic treatments, this review attempts to compile and assess the data from pertinent systematic reviews and meta-analyses. Methods The systematic evaluation of repetitive transcranial magnetic stimulation for post-stroke depression was collected by searching CNKI, VIP, Wanfang Database, CBM, PubMed, Web of Science, and Cochrane Library. The retrieval time is from database construction to September 2022. After selection, the included literature was evaluated for methodological quality, reporting quality, and evidence quality using AMSTAR2, PRISMA statements, and the GRADE system. Results There were a total of 13 studies included, with 3 having generally comprehensive reporting according to the PRISMA statement, 8 having some reporting issues, 2 having pretty substantial information issues, and 13 having extremely poor methodological quality according to the AMSTAR2 . The GRADE was used to grade the quality of the evidence, and the included literature had 0 high-level evidence, 8 medium-level evidence, 12 low-level evidence, and 22 very low-level evidence. Limitations The results of this study are from researchers' subjective evaluation and only qualitative analysis, not quantitative evaluation. Although repeated cross-evaluation of researchers is carried out, the results will be personal. The interventions included in the study were complex, and it was impossible to analyze their effect values quantitatively. Conclusion Patients with post-stroke depression may benefit from repetitive transcranial magnetic stimulation. However, in terms of the quality of the reports, the methodology, and the quality of the evidence, published systematic evaluations/meta-analyses are of low quality. We list the drawbacks of the current clinical trials of repetitive transcranial magnetic stimulation for post-stroke depression as well as potential therapeutic mechanisms. This information may serve as a guide for future clinical trials aiming to establish a solid foundation for the clinical efficacy of repetitive transcranial magnetic stimulation in the treatment of post-stroke depression.